Accuracy of Lumbosacral Pedicle Screw Placement in Dogs: A Novel 3D Printed Patient-Specific Drill Guide versus Freehand Technique in Novice and Expert Surgeons - Bongers, Jos J.; Wilkinson, Nathan; Kurihara, Manabu; Bridges, Janis P.; Baltzer, Wendy; Worth, Andrew J. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to compare the accuracy of pedicle screw placement at the canine lumbosacral junction using a novel unilateral three-dimensional printed patient-specific guide (3D-PSG) versus a freehand drilling technique. Additionally, accuracy of screw placement between a novice and an experienced surgeon was determined.Study Design Preoperative computed tomography images from 20 lumbosacral cadaveric specimens were used to design a novel unilateral 3D-PSG for the L7 and sacral vertebrae which was printed in acryl-nitrile butadiene styrene plastic. A novice and an expert surgeon each placed 3.5mm cortical screws in 10 cadavers; on the left using the unilateral 3D-PSG and by the freehand (anatomic landmark) technique on the right.Results Sixty screws were placed using the unilateral 3D-PSG and 60 using the freehand technique. There was no statistical difference in accuracy for the comparison between methods performed by the expert (p = 0.679) and novice (p = 0.761) surgeon, nor between an expert and novice surgeon overall (p = 0.923). Unexpectedly, the use of a unilateral 3D-PSG increased variability for the expert surgeon in our study (p = 0.0314).Conclusion Using a novel unilateral 3D-PSG did not improve the accuracy of screw placement for lumbosacral stabilization by a novice surgeon compared with an expert surgeon in lumbar spine surgery. This may reflect a suboptimal PSG design.
Keywords: accuracy; 3D printed; lumbosacral; screw; patient-specific